Cult of the mother Goddess: fictions and facts - Madhusudan Mishra (ed.) (Delhi : Eastern Book Linkers, 2013)
Papers presented at the national seminar on "The Cult of the Mother Goddess: Fictions and Facts", held at K.K.S. Women's College in 2008.
Keywords: Mother Goddesses; Hinduism; Religion